2005
DOI: 10.1108/02635570510633266
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ERP system's functionality with discrete event simulation

Abstract: Purpose-To develop a methodology to augment enterprise resource planning (ERP) systems with the discrete event simulation's inherent ability to handle the uncertainties. Design/methodology/approach-The ERP system still contains and uses the material requirements planning (MRP) logic as its central planning function. As a result, the ERP system inherits a number of shortcomings associated with the MRP system, including unrealistic lead-time determination. The developed methodology employs bi-directional feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…They are some kind of extension to the existing information system. This is a similar thesis that has been already confirmed by Moon and Phatak (Moon and Phatak, 2005). They demonstrated that the limited planning functionality of the Enterprise Resource Planning (ERP) system can be complemented by the discrete-event simulation models.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…They are some kind of extension to the existing information system. This is a similar thesis that has been already confirmed by Moon and Phatak (Moon and Phatak, 2005). They demonstrated that the limited planning functionality of the Enterprise Resource Planning (ERP) system can be complemented by the discrete-event simulation models.…”
Section: Introductionsupporting
confidence: 66%
“…Greasley and Barlow (Greasley, 2005) analyzed a business process approach to a change in a custody-ofprisoner process. Ozbay and Bartin (Ozbay and Bartin, 2003) studied an incident management situation with the Arena simulation package. Hlupic and de Vreede (Hlupic and de Vreede, 2005) used simulation modelling and analysis to reduce the risk of business process innovation in an outpatient's department.…”
Section: Business Process Modelling and Simulation Modellingmentioning
confidence: 99%
“…Moon and Phatak (2005) noted that simulations can often capture and describe the complex interactions within a particular manufacturing or supply-chain system where traditional analytical methods fail. On the other hand, mathematical techniques can assist in the development of parameters in a modelling effort, how individual agent characteristics affect a system, and identification of agents to develop an agent-based modelling (ABM) effort (Surana et al 2005).…”
Section: Agent-based Modelling In Supply-chain Fulfillmentmentioning
confidence: 99%
“…One, simulations are developed offline and separate from enterprise software packages (Yoon and Shen 2006), limiting observations to single event analysis. Moon and Phatak (2005) found that traditional simulation models are usually not built for repetitive and continuous usage partially due to the laborious data collection process. Difficulty in automatic collection of data and continuous update of the data for the built simulation model discourages further usage of the initial model.…”
Section: Agent-based Modelling In Supply-chain Fulfillmentmentioning
confidence: 99%
“…The biggest challenge of teaching the fundamentals of the ERP systems in Universities is to teach it as a whole since the essence of the ERP system is its integrative nature [14]. Institutions are looking for new tools, methodologies and solutions to multifaceted problems.…”
Section: Discussionmentioning
confidence: 99%